2017
DOI: 10.1007/s11121-017-0812-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Highs and Lows of the Collaborative Relationship Between Technical Assistance Providers and Prevention Implementers

Abstract: The PROSPER model uses a three-tiered community partnership, university researcher, and Cooperative Extension-based technical assistance system to support the delivery of evidence-based interventions in communities. This study examines the trajectory and predictors of the collaborative relationship between technical assistance providers and community teams across the three phases of organization, implementation, and sustainability. Members of 14 PROmoting School-university-community Partnerships to Enhance Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…Dimensions of Coalition Check-Up implementation quality include (1) coalition-TA provider collaborative working relationship, (2) action plan quality and implementation, and (3) fidelity to the Coalition Check-Up model. The collaborative working relationship between the TA provider and coalition leader/coalition will be assessed with measures drawn from Chilenski, Feinberg, and Welsh’s prior work on PROSPER [ 13 , 43 , 44 ]. The scale captures trust between the TA provider and the coalition, empowerment vs. providing information-only, and mutual respect.…”
Section: Methodsmentioning
confidence: 99%
“…Dimensions of Coalition Check-Up implementation quality include (1) coalition-TA provider collaborative working relationship, (2) action plan quality and implementation, and (3) fidelity to the Coalition Check-Up model. The collaborative working relationship between the TA provider and coalition leader/coalition will be assessed with measures drawn from Chilenski, Feinberg, and Welsh’s prior work on PROSPER [ 13 , 43 , 44 ]. The scale captures trust between the TA provider and the coalition, empowerment vs. providing information-only, and mutual respect.…”
Section: Methodsmentioning
confidence: 99%
“…Chilenski and colleagues found that levels of collaboration were relatively high during the planning phase of a community prevention project, decreased during implementation, and then increased again during the sustainability phase. 11 Such findings underscore the importance of tailoring TA to the unique needs of stakeholders that typically change throughout different phases of planning and implementation.…”
Section: Effects Of Technical Assistance On Implementationmentioning
confidence: 99%
“…Moreover, there has been consistent interest in ensuring that TA systems themselves are based on comparative effectiveness research. 6,9,11 However, empirical research on the effects of TA on general youth-focused programming is emergent at best, with significant gaps in research on the provision of TA to support the implementation of SOC strategies.…”
mentioning
confidence: 99%
“…Children's Trust developed this coaching model based on research identifying community coaching as an implementation support strategy (Bauer et al, 2015; Chilenski et al, 2018) and prior organizational experience using coaches to support the implementation of evidence‐based programs. Due to the system nature of Triple P and limited resources available from funders, it was necessary to design a coaching mechanism that shared implementation best practices with a large number of diverse stakeholders.…”
Section: Developing the Community Capacity Coach Modelmentioning
confidence: 99%